Why countries fail. The origins of power, prosperity and poverty - Dávila Picón, Dennis David (2025)
We review “Why countries fail. The Origins of Power, Prosperity and Poverty”, one of the books in which Daron Acemoglu and James Robinson present their work exploring the causes of prosperity and failure of nations. This book, which was published in 2012, proposes alternative explanations to the traditional ones on economic development and presents a theory based on the role of political and economic institutions. Daron Acemoglu, Simon Johnson and James A. Robinson were awarded the Nobel Prize in Economics, a prize given in recognition of outstanding contributions to humanity by the Nobel Foundation in Sweden.